2016
DOI: 10.1111/infa.12141
|View full text |Cite
|
Sign up to set email alerts
|

Empty Looks or Paying Attention? Exploring Infants' Visual Behavior during Encoding of an Elicited Imitation Task

Abstract: Recently, there has been an increased interest in the relationship between looking time during encoding and subsequent memory performance in imitation tasks. Hitherto, the results have been inconclusive: one line of research supporting the link between looking time and performance and another line finding no relation. The existing studies may, however, have been restricted by using small samples, limited looking time measures, and short retention intervals. We here examined the relationship between the encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…For instance by focusing on what is happening during the encoding of an event, perhaps with a special focus on the boundaries. In order to investigate whether increased processing occurs during event boundaries one would have to look beyond raw looking time data, given the fact that the relationship between processing and looking time during encoding may not necessarily be linear (e.g., Òturai, Kolling & Knopf, ; Sonne, Kingo & Krøjgaard, ). In addition, future studies should investigate whether these results would replicate using more daily‐life stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…For instance by focusing on what is happening during the encoding of an event, perhaps with a special focus on the boundaries. In order to investigate whether increased processing occurs during event boundaries one would have to look beyond raw looking time data, given the fact that the relationship between processing and looking time during encoding may not necessarily be linear (e.g., Òturai, Kolling & Knopf, ; Sonne, Kingo & Krøjgaard, ). In addition, future studies should investigate whether these results would replicate using more daily‐life stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the introduction we know that distorted versions of TV shows for kids have an effect on infants’ looking time during encoding ( Anderson et al, 1981 ; Pempek et al, 2010 ), but we do not know whether this affects later memory. Other studies, however, have shown that looking time during the encoding of an event is not necessarily a strong predictor to later memory (e.g., Sonne et al, 2016b ). We therefore wanted to investigate whether our results could be explained by differences in looking time during encoding.…”
Section: Studymentioning
confidence: 88%
“…Another measure that may reveal whether participants are attentively looking at the displayed stimuli is pupil dilation ( Eckstein et al 2017 ). Pupil dilation is modulated by brain structures that control physiological arousal and attention and, as such, can be used as a measure of cognitive effort and task difficulty across problem-solving tasks (e.g., Beatty 1982 ; Boersma et al 1970 ; Chevalier et al 2012 ; Eckstein et al 2017 ; Krøjgaard et al 2020 ; Sonne et al 2016b ), in both children and adults. Increased pupil dilation correlates with increased subjective task difficulty and cognitive effort and has recently been shown in adults during a proactive interference task ( Johansson et al 2018 ), in which goal-relevant information competed with goal-irrelevant information in working memory.…”
Section: Prioritizing Truly Relevant Over Seemingly Relevant Informat...mentioning
confidence: 99%